Double Rotor Switched Reluctance Machine with Segmented Rotors - Guo, Teng (My University, 2015)
Double rotor machines, appearing in versatile forms and configurations thanks to the great flexibility of having a pair of rotors, are seen in a number of applications. Double rotor machines show promising prospect in the application of advanced hybrid electric vehicle powertrains due to the requirement of dual electro-mechanical ports in such systems. Integrating these powertrain systems with double rotor machines not only brings design freedom of laying out components, but also reduces number of parts and thus improves compactness. The switched reluctance type double rotor machines, offering unique characteristics of having a simple structure and no permanent magnets, are strong candidates for high performance applications. In this thesis, a family of double rotor switched reluctance machine with segmented rotors is proposed and studied. Compared to double rotor switched reluctance machines with a more conventional structure, the proposed designs exhibit potentials of achieving higher compactness and performance. A prototype double rotor machine of the segmented rotor design is constructed and tested to benchmark an existing double rotor switched reluctance machine. The experiment results show that the proposed design is able to achieve the same output with similar or higher efficiency than the benchmark machine, while occupying only about 60% of overall volume. The double segmented rotor switched reluctance machine demonstrates to be a promising double rotor topology and is worth further research.
Keywords: Switched reluctance machine; Double rotor electric machine